AD, Volume 39, n° 2, 2014 - Full Issue (Africa Development, 2021)
Contents / Sommaire Technology Transfer, Foreign Direct Investment and Economic Growth in Nigeria Omojola Omowumi Awosusi & Olawumi Dele Awolusi...........1 Of Fundamental Change and No Change: Pitfalls of Constitutionalismand Political Transformation in Uganda 1995-2005 Godfrey B. Asiimwe....................... 21 Développement de l’orpaillage et mutations dans les villagesaurifères du sud-est du Sénégal Bakary Doucouré............................ 47 Sous-information et sous-développement en Afrique Alain François Loukou...................69 Histoire et mémoire de Gorée dans la traite atlantique Pape Chérif Bertrand Bassène.................. 93 Opposition Politics and Electoral Democracy in Cameroon(1992-2007) George Ngwane....................103 Renaissance et environnement juridique Maty BB-Laye Diakhaté........................117 Managing Religious Conflicts in Nigeria: The Inter-Religious Mediation Peace Strategy Mashood Omotosho..........................133 ‘Ties that Bind and Differences that Divide’: Exploring the Resurgenceof Ethno-Cultural Identity in Nigeria Edward Nsemba Lenshie.........................153